The Effectiveness of Anti-Bullying Programs in Reducing Bullying Behavior in Junior High Schools: Efektivitas Program Anti-Perundungan dalam Menurunkan Perilaku Perundungan di Sekolah Menengah Pertama - Sena Agustin; Qotrun Nida; Dinar Sugiana Fitrayadi (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
Bullying remains a persistent problem affecting school safety, including at SMP Negeri 5 Kota Serang where an anti-bullying program has been implemented. This study evaluates the program’s effectiveness in reducing students’ bullying behavior. A quantitative descriptive-evaluative cross-sectional design was used. The population comprised 493 eighth-grade students in the 2024/2025 academic year, with 83 students selected as the sample. Data were collected through a 4-point Likert questionnaire measuring the Anti-Bullying Program (X) and Bullying Behavior (Y). Validity testing yielded 32 valid items for X and 33 for Y, while reliability was high (αX=0.841; αY=0.877). Data analysis included normality testing, simple linear regression (t-test on the regression coefficient), and effectiveness measurement using Likert Summated Rating (LSR). Results indicated normal data distribution (Sig.=0.200>0.05). The anti-bullying program showed a negative but nonsignificant effect on bullying behavior (t=-1.526; p=0.131). LSR analysis produced a total score of 14,488 with a 67% effectiveness rate, exceeding the median quartile (Q2), thus categorizing the program as effective. Nevertheless, verbal bullying and negative peer influence remain notable challenges. Overall, the program is practically effective, but its statistical impact is not yet strong, requiring stronger monitoring, follow-up procedures, and positive peer involvement.